Effects of evaporation parameters on recuperative transcritical organic Rankine cycle using binary mixture fluids. (25th August 2020) - Hsieh, Jui-Ching; Cheng, Chu-Hong
Abstract: In this study, thermodynamic analysis was performed on basic and recuperative transcritical organic Rankine cycles by using five pure and six mixed fluids. The effects of evaporation parameters on the first- and second-law efficiencies ( ηI and ηII ) as well as power output were investigated. The results indicate that a recuperator had a positive effect on the ηI and ηII and negative effects on the specific power. The total irreversibility of the system was improved by the recuperator. However, the total irreversibility considerably increased with an increase in the expander inlet temperature ( Texp, in ) due to the significant increase in irreversibility in the condenser, particularly for working fluids with low critical temperatures, namely R134a, R1234yf and R290, and low proportions of R245fa and R600a in mixed fluids. For both the pure and mixed fluids, the specific power linearly increased with an increase in the expander inlet pressure ( Pexp, in ) and Texp, in . However, with an increase in Pexp, in, the ηI and ηII first increased and then decreased. Finally, for ηI and ηII, the effect of the recuperator increased with an increase in Texp, in even though the recuperator had a relatively small effect on the working fluids with high critical temperature, especially when Pexp, in was high.